2021
DOI: 10.1016/j.scog.2020.100192
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between disability self-awareness and cognitive and daily living function in schizophrenia

Abstract: We investigated the relationship between disability self-awareness and cognitive and daily living functions in 49 patients with schizophrenia. The World Health Organization Disability Assessment Schedule 2.0 (WHODAS) self-report was used to identify patient-rated global function. A clinician-rated measure of global function was obtained using the Personal and Social Performance Scale (PSP); disability self-awareness was calculated using two global function scores. The Positive and Negative Syndrome Scale (PANS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…It is natural for the ratio of under-estimator to over-estimator to change with sampling. Furthermore, previous studies have reported that higher levels of daily living function and higher cognitive abilities are associated with overestimation of their own cognitive impairments [ 32 ]. The participants in this study were outpatients with stable clinical status, and most of them achieved all categories of the WCST.…”
Section: Discussionmentioning
confidence: 99%
“…It is natural for the ratio of under-estimator to over-estimator to change with sampling. Furthermore, previous studies have reported that higher levels of daily living function and higher cognitive abilities are associated with overestimation of their own cognitive impairments [ 32 ]. The participants in this study were outpatients with stable clinical status, and most of them achieved all categories of the WCST.…”
Section: Discussionmentioning
confidence: 99%
“…The negative behavior and emotions experienced by RVB patients with schizophrenia result from interpreting events; they experience in their lives. In addition, RBV occurs due to extreme conditions that result in maladaptive coping mechanisms [12].…”
Section: Discussionmentioning
confidence: 99%
“…CBT therapy brought several impacts, such as cognitive distortions, disturbing feelings to emotions without causing loss of self-awareness, social problems, and physiological problems. Kim et al (2020) explain that patients' inability to recognize maladaptive thoughts and behaviors contributes significantly to the emergence of positive symptoms [12]. This condition disables them to find adaptive coping to deal with the situation experienced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients were divided according to their self-assessment of their own abilities. The accuracy of the evaluation was assessed by comparing the patients’ self-reported score of function with an informant-reported score, using traditional self-assessment techniques of functional status ( Bowie et al, 2007 ) and recent studies ( Kim, Jung, et al, 2020 ). The self-reported score was evaluated by using the Social Functioning Scale (SFS) ( Birchwood et al, 1990 ), and the informant-reported score was evaluated using the Life Assessment Scale for Mental Illness (LASMI) ( Iwasaki et al, 1994 ), which is frequently used in Japan.…”
Section: Methodsmentioning
confidence: 99%